Unconfined Compressive Strength and Damage Evolution in Geopolymer-Stabilized Clay Shale: Role of Temperature and Alkali Activator Ratio - Willis Diana; Edi Hartono; Agus Setyo Muntohar; Nurza Purwa Abiyoga (Journal of the Civil Engineering Forum, 2026)
Exposed clay shale is highly susceptible to weathering and rapid strength degradation, which often leads to slope and earth-structure instability. Geopolymer-based soil stabilization has emerged as a promising method to improve the mechanical properties of such problematic materials. However, this chemical stabilization process is sensitive to environmental conditions, particularly temperature fluctuations. The performance of geopolymer-stabilized clay shale under elevated-temperature conditions remains insufficiently investigated, particularly in tropical regions such as Indonesia, where temperatures can fluctuate between 25◦C and 40◦C, and the exposed ground surface may reach up to 60◦C during the dry season because of intense solar radiation. This study evaluates the effectiveness of fly ash–based geopolymer in stabilizing clay shale under temperature variations ranging from 26◦C to 60◦C. A series of laboratory experiments was conducted using two alkali activator ratios (Na2SiO3:NaOH), namely 2.0 (Ratio A) and 2.5 (Ratio B). Mechanical performance was assessed through unconfined compressive strength (UCS) tests, stress–strain analysis, and energy-based damage evolution to quantify strength development and failure behavior. The results indicate that temperature is the dominant factor controlling strength development. A 10◦C increase in curing temperature resulted in a 40–60% increase in UCS, whereas variations in the alkali activator ratio produced only a 15–20% increase. The highest strength amplification, reaching 16 times that of untreated soil, was achieved using Ratio B at 60◦C, while Ratio A showed strength stagnation above 50◦C. Microstructural observations suggest that elevated temperatures accelerate geopolymer gel formation, leading to higher initial stiffness and an expanded elastic region. However, this also resulted in more brittle behavior, characterized by a higher brittleness index and rapid post-peak damage propagation for Ratio B, whereas Ratio A exhibited greater ductility. Overall, higher curing temperatures increased the dissipated energy at failure and revealed a clear strength–ductility trade-off. These findings provide insights for optimizing geopolymer stabilization of clay shale, particularly for geotechnical applications in tropical environments where elevated in situ temperatures are common.